Effectiveness of Educational Program on Nurses Knowledge about Ovarian Cancer in Baghdad City Hospitals - Alaa Qahtan Mohamed Ali, Aqeel Habeeb Jasim (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ovarian cancer affects a lot of people all over the world, and it has a lot of physical and psychological consequences. However, there are many misconceptions, symptoms are usually missed, and diagnosis is frequently delayed Meridith, B.(2018( .therefore enriching nurses knowledge about ovarian cancer very essential in order to improve nurses services for women with this dangerously diffused type of cancer. Objectives : To determine the effectiveness of Educational program on nurses knowledge about ovarian cancer Methods : A quasi-experimental,(two groups pretest –posttest ) control group and study design is carried out in order to achieve objectives of the study by using the evaluation approach and implementation of education program at (Baghdad teaching hospital, oncology teaching hospital, Alyarmok teaching hospital).from to 7 September to 18 December, Non- probability a purposive of (72) of nurses (36) study group and (36) control group has been selected for the present study from three teaching Hospitals in Baghdad City from to 7 September to 18 December. The data collection tool contains (57) multiple- choice questions of nurses knowledge about ovarian cancer . Results: The study showed a clear improvement after educational program in the information of nurses ,according to the results. Conclusion :The study concluded that the nurses working in the field that deals with ovarian cancer have insufficient knowledge about ovarian cancer . The program has effect on nurses level of knowledge and practice about ovarian cancer during the two period of test ,the study sample have low level of knowledge (pretest) implementation of educational program and the level of ascend to high level (posttest) implementation of educational program